Motivation and attitudes in learning English: a case study of form 3 students in Sekolah Menengah Kebangsaan Tuanku Lailatul Shahreen Kangar Perlis / Azia Razwa Abdul Razak - Abdul Razak, Azia Razwa (Faculty of Education, 2014)
This research was conducted to find out the types of motivation and attitudes that Form 3 students of Sekolah Menengah Kebangsaan Tuanku Lailatul Shahreen have in learning English Language. Three motivational constructs were tested, instrumental, personal and integrative motivations based on Brown’s (2001) and Atef & Munir’s (2009) work. Four aspects of learners’ attitudes 1) toward English Language in social context, 2) toward English Language in educational context, 3) toward English Language and 4) toward English speaking culture were studied. A set of questionnaire was distributed to 48 respondents from Form 3 students of Sekolah Menengah Kebangsaan Tuanku Lailatul Shahreen. From the research, instrumental motivation recorded the highest mean score while integrative motivation recorded the lowest mean score. Attitude wise, the results showed that respondents have positive attitudes toward English Language. At the end of this research, researcher presented recommendations, suggestions and implications that could be implemented in future research as well as to be implemented in classroom instructions.